Potensi Madrasah di Era Peradaban Modern - Shodiq, Muhammad Ja’far (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2022)
Fall up changes and improvements in accordance with the dynamics of the changes of the times attached to the institution of the madrasa. So the potential Madrasah in the face of the modern era with the development of Science and technology to be slightly open even though in fact the potential is difficult to be raised.The approach in this study using a philosophical approach. The characteristics of this approach emphasize the fundamental structure and the basic ideas as well as avoiding the details of the issues less relevant. Data collection method used in this research is documentation, within the meaning of the study of documents written, both derived from primary and secondary data sources. Analysis of data was done beginning with the reduction process (selection) data, a description of the data (compiling data narrative), and inference of data.The results showed that the potential of the Madrasah in modern civilization can be resolved by accepting the progress of the modern education system, to develop educational activities that are open based on the demands of the times, build the power of innovation simultaneously, as well as the development of qualifications knowledge of the dimensions of Faith and Science and technology as well as others.Keyword: Potential; Madrasah; The Modern Era. Abstrak Jatuh bangun perubahan dan penyempurnaan sesuai dengan dinamika perubahan zaman melekat pada institusi Madrasah. Sehingga potensi Madrasah dalam menghadapi era modern dengan perkembangan Iptek menjadi sedikit terbuka walaupun pada kenyataannya potensi tersebut sulit untuk dimunculkan.Pendekatan dalam penelitian ini menggunakan pendekatan filosofis. Karakteristik pendekatan ini menekankan fundamental structure dan ide-ide dasar serta menghindari detail-detail persoalan yang kurang relevan. Metode pengumpulan data yang digunakan dalam penelitian ini adalah dokumentasi, dalam arti menelaah dokumen-dokumen tertulis, baik yang berasal dari sumber data primer maupun sekunder. Analisis atas data dilakukan diawali dengan proses reduksi (seleksi) data, deskripsi data (menyusun data naratif), dan penyimpulan data.Hasil penelitian menunjukan bahwa potensi Madrasah dalam peradaban modern dapat dituntaskan dengan menerima kemajuan sistem pendidikan modern, mengembangkan kegiatan-kegiatan pendidikan yang terbuka berbasis tuntutan zaman, membangun daya inovasi yang simultan, serta pengembangan kualifikasi pengetahuan dari dimensi Imtaq dan Iptek serta lain sebagainya.Kata Kunci: Potensi; Madrasah; Era Modern.